Virtual Reality in Psychological, Medical and Pedagogical Applications - Eichenberg, Christiane (IntechOpen, 2012)
This book has an aim to present latest applications, trends and developments of virtual reality technologies in three humanities disciplines: in medicine, psychology and pedagogy. Studies show that people in both educational as well as in the medical therapeutic range expect more and more that modern media are included in the corresponding demand and supply structures. For the Internet and various mobile media, associated research and application projects now have fixed key words such as "E-learning" and "E-Mental Health" or "M-Learning", "M-Mental Health". This book aims to contribute to the current state of the corresponding efforts in the area of ??further promising technology - the Virtual Reality - designed to give an overview and secondly to provide a stimulus on specific projects, associated with the hope of giving to scientists and practitioners from the humanities an impulse for their own (further-) development, evaluation and implementation of various VR scenarios in the education and health sectors.